2017
DOI: 10.6004/jnccn.2017.7003
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for Brain Metastases: Changing Practice Patterns and Disparities in the United States

Abstract: Background: Management of brain metastases typically includes radiotherapy (RT) with conventional fractionation and/or stereotactic radiosurgery (SRS). However, optimal indications and practice patterns for SRS remain unclear. We sought to evaluate national practice patterns for patients with metastatic disease receiving brain RT. Methods: We queried the National Cancer Data Base (NCDB) for patients diagnosed with metastatic non-small cell lung cancer, breast cancer, colorectal cancer, or melanoma from 2004 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 28 publications
1
38
1
Order By: Relevance
“…As evidence supporting the use of SRS for managing brain metastases grows, we would expect SRS rates to rise . While SRS was less frequently used in regional centres, patients living in regional areas were as likely to receive SRS as patients living in metropolitan areas.…”
mentioning
confidence: 99%
“…As evidence supporting the use of SRS for managing brain metastases grows, we would expect SRS rates to rise . While SRS was less frequently used in regional centres, patients living in regional areas were as likely to receive SRS as patients living in metropolitan areas.…”
mentioning
confidence: 99%
“…Kann et al . identified several progressively widening sociodemographic disparities in the adoption of SRS in the United States. While the reasons for these disparities are not well quantified, the lack of availability of specialized treatment machines and human skills and resources are a reasonable hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…With ring-based machines, that is not a concern and it is practical to envision that SRS delivery with head flexion could be delivered in an efficient and safe manner with limited staffing and resources. Kann et al 27 identified several progressively widening sociodemographic disparities in the adoption of SRS in the United States. While the reasons for these disparities are not well quantified, the lack of availability of specialized treatment machines and human skills and resources are a reasonable hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] However, although the NCDB captures approximately 70% of newly diagnosed cancer cases, to our knowledge melanoma is the least well-captured cancer type: it is estimated that only approximately one-half of all cases are represented by this database. Many studies have used the NCDB due to its robust reporting of information regarding individual cases, including treatment follow-up, quality-of-care metrics, and greater number of cases captured compared with alternative databases.…”
Section: Limitationsmentioning
confidence: 99%
“…Many studies have used the NCDB due to its robust reporting of information regarding individual cases, including treatment follow-up, quality-of-care metrics, and greater number of cases captured compared with alternative databases. [21][22][23][24] However, although the NCDB captures approximately 70% of newly diagnosed cancer cases, to our knowledge melanoma is the least well-captured cancer type: it is estimated that only approximately one-half of all cases are represented by this database. 25 This is most likely attributed to the fact that early-stage melanoma is more likely to be diagnosed outside of the hospital setting and subsequently missed by the NCDB; however, patients with an initial melanoma diagnosis in the community later may be treated in the hospital setting and therefore be captured.…”
Section: Limitationsmentioning
confidence: 99%